An Ethnoscience Study in Chemistry Learning to Develop Scientific Literacy - Dewi, C. A.; Khery, Y.; Erna, M. (Jurnal Pendidikan IPA Indonesia, 2019)
The low scientific literacy index of Indonesian students is due to lack of attention to socio-cultural environment. Also, there are still many contents, the context, and processes in chemistry learning that have not been achieved as learning resources for developing the domain of scientific literacy into four main areas. They are science content, competence, or science process, the context of the application of science and attitude. This study intended to develop scientific literacy through ethnoscience pedagogic in chemistry learning. The method of this study was qualitative descriptive with the retrieval of data through direct observation, questionnaires, and interviews. The results of the study showed that the needs of: (1) the curriculum emphasis on the development of chemistry literacy for students; 2) the skills of chemistry lecturers in designing learning programs by using local potential in their respective regions; (3) the early discussion on the material coverage the basic concepts of chemistry; and (4) the emphasis not only on chemistry content but also on context, processes, and attitudes. Thus it can be concluded that the development of scientific literacy needs to be done by focusing on the preparation of future generations of scientific literacy with curriculum content that pays attention to culture and daily life to make it more contextual.